Dampak Dehidrasi Saat Masa Kehamilan - Erlicha Paramitha Maryanto (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Water is important for a person and has a function to maintain cell hemostasis. The composition of fluids in the body changes during pregnancy to support the growth and development of the fetus in the womb. Physiological conditions experienced by pregnant women can affect the balance of body fluids which will affect the hydration status of pregnant women. In Indonesia, it is found that 57.1% of pregnant women are dehydrated. Dehydration is a condition where the body loses more fluids than the fluids intake. This study used a literature study method with the keywords